Manajemen Pembelajaran Berbasis Studi Kasus (Case Method) - Marmoah, Sri - (Perspektif Ilmu Pendidikan, 2022)
Abstract: Policies regarding key performance indicators have encouraged them to be able to implement problem-based and collaborative learning. Therefore, there is need for innovation in learning with learning methods empower students is cases method. The purpose of this research is to find out the management of learning in case studies of college level students who use expost facto. This study obtained data through observation, tests and questionnaires. The sample in this study was 132 students of the Elementary School Teacher Education study program. The results of the planning stage of the questionnaire with a percentage of 75.48% in the good category, the implementation stage by obtaining a percentage of 92.30% in the very good category, and the evaluation stage by obtaining a percentage of 87.90% in the very good category. The results of case study-based learning that are applied in class management courses, which are acceptable to students, are considered helpful and effectively applied in learning. Keywords: Case Method, Learning Management